REPRESENTACIÓN DE UNIDADES TERMINOLÓGICAS: EL MODELO DE TÉRMINO WÜSTERIANO - Adelstein, Andreína (Organon, 2012)
The purpose of this paper is to show the linguistic character of the term concept and its explanatory modelin Wüster's work. The paper explains the steps in the denomination process and its representation model. The analysisof the variation registered in the texts relative to the concept of term itself and of its model, as well as the study of itstheoretical and methodological consequences, is used to detemine the type of linguistic statute of the term in Wüster'sopus.